Validation for EuroSCORE II in the Indonesian cardiac surgical population: a retrospective, multicenter study - Kurniawaty, Juni; Setianto, Budi Yuli; Widyastuti, Yunita; Supomo, Supomo; Boom, Cindy Elfira; Ancilla, Cornelia (Taylor and Francis Ltd., 2022)
Background: In 2011, the European System for Cardiac Operative Risk (EuroSCORE) II was created as an improvement of the additive/logistic EuroSCORE for the prediction of mortality after cardiac surgery. Objective: To validate EuroSCORE II in predicting the mortality of open cardiac surgery patients in Indonesia. Methods: We performed a multi-center retrospective study of cardiac surgery patients from three participating centers (Dr. Sardjito Hospital, Kariadi Hospital, and Abdul Wahab Sjahranie Hospital) between January 1st, 2016, and December 31st, 2020. Discrimination and calibration tests were performed. Results: The observed mortality rate was 9.5 (73 out of 767 patients). The median EuroSCORE II value was 1.13. The area under the curve for EuroSCORE II was 0.71 (95 CI: 0.65–0.77), suggesting fair discriminatory power. Calibration analysis suggested that EuroSCORE II underestimated postoperative mortality. Gender, age, chronic pulmonary disease, limited mobility, NYHA, and critical pre-operative state were significant predictors of post-cardiac surgery mortality in our population. Conclusion: This study suggested that the EuroSCORE II was a poor predictor for postoperative mortality in Indonesian patients who underwent cardiac surgery procedures. Therefore, EuroSCORE II may not be suitable for mortality risk prediction in Indonesian populations, and surgical planning should be decided on an individual basis. © 2022 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.